2022
DOI: 10.22146/jpti.73198
|View full text |Cite
|
Sign up to set email alerts
|

Induced Resistance Mechanism of Twisted Disease Suppression of Shallot by Bacillus spp.

Abstract: Plant Growth Promoting Rhizobacteria has been known for its ability to induce plant resistance on shallot against twisted disease. Its ability as a bioprotectant agent is estimated to be comparable to the efficacy of Trichoderma which is currently widely used as a biological control agent.. This study aims to determine the content of jasmonic acid, salicylic acid, peroxidase, and disease suppression in shallot by application of Bacillus velezensis B-27, Bacillus cereus RC76, and application with combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…The suppression of twisted disease based on the disease intensity of five shallot varieties in all treatments ranged from 71.85% to 77.78% (Table 3). The ability of B. velezensis B-27 and B. cereus RC76 in combination to suppress twisted disease in the greenhouse, based on the study by Wulan et al (2022) showed that the twisted disease intensity was reduced by up to 90% with the bulb-dipping method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The suppression of twisted disease based on the disease intensity of five shallot varieties in all treatments ranged from 71.85% to 77.78% (Table 3). The ability of B. velezensis B-27 and B. cereus RC76 in combination to suppress twisted disease in the greenhouse, based on the study by Wulan et al (2022) showed that the twisted disease intensity was reduced by up to 90% with the bulb-dipping method.…”
Section: Resultsmentioning
confidence: 99%
“…The bulbs of five shallot varieties were dipped in a bacterial combined suspension of B. velezensis B-27 and B. cereus RC76 at a density of 10 8 CFU/mL with a ratio of 1:1. Each variety was dipped in 300 mL of the bacterial combination added to 3000 mL of water for 30 min, then air-dried (Wulan et al, 2022). The five shallot varieties were then planted in beds with a spacing of 20 × 15 cm.…”
Section: Inoculation Of Pathogenic Fungi In the Greenhousementioning
confidence: 99%
“…Furthermore, the treatment of B. velezensis had 71% similarity of fungal community compared to the treatments of B. cereus RC76 at the beginning of planting can induce plant resistance and suppress twisted disease by enhancing the accumulation of jasmonic acid (Wulan et al 2022). Jasmonic acid can activate plant resistance through the ISR signalling pathway, which causes priming for enhancing host defence gene expressions such as pathogenesis related (PR) 1, PR2, PR5, and plant defensin (PDF 1.2) (Niu et al 2011).…”
Section: Effect Of Pgpr On the Production Of Shallot Plantsmentioning
confidence: 94%
“…The use of B. velezensis by soaking and spraying application by Rahma et al (2020), reported that B. velezensis was able to suppress twisted disease and purple spots development on shallot plants by 67% and increase plant growth and protect shallot bulbs postharvest. Wulan et al (2022) reported that the use of B. velezensis reduced disease development by 89%, with disease intensity and incidence of 4% and 4%, respectively.…”
Section: Introductionmentioning
confidence: 99%